2018
DOI: 10.21873/anticanres.12764
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix–receptor Interaction Signaling Genes Associated with Inferior Breast Cancer Survival

Abstract: These findings suggest that HMMR and SDC1 involved in the ECM-receptor interaction signaling pathway could act as effective independent prognostic biomarkers for breast ductal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
2
41
0
Order By: Relevance
“…Therefore, CCND1 may be an attractive therapeutic target in cancer. The FOXJ1 gene was o verexpressed in the anaplastic ependymoma cases in our study and has been reported to have the highest levels in posterior fossa ependymoma group B tumors [22]. The highly expressed genes in this research, such as BOC, PRC1, RFX2, FOSL1, EPHA2, and IGF2BP1, were reported as potential therapeutic molecular targets of ependymoma [23].…”
Section: Methodssupporting
confidence: 60%
“…Therefore, CCND1 may be an attractive therapeutic target in cancer. The FOXJ1 gene was o verexpressed in the anaplastic ependymoma cases in our study and has been reported to have the highest levels in posterior fossa ependymoma group B tumors [22]. The highly expressed genes in this research, such as BOC, PRC1, RFX2, FOSL1, EPHA2, and IGF2BP1, were reported as potential therapeutic molecular targets of ependymoma [23].…”
Section: Methodssupporting
confidence: 60%
“…The extracellular matrix (ECM), composed of polysaccharides and brous proteins, is an important structural component of the tumor microenvironment. Previous studies have shown that dysregulation of the extracellular matrixreceptor interaction signaling pathway plays a vital role in regulating tumor invasion and metastasis [30] . Not only that, focal adhesion (FA) promotes cell traction by associating the ECM bound to the transmembrane integrin molecule with the actin cytoskeleton, which also plays an important role in cell migration dynamics [31,32] .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Fig. 2B, KEGG pathway enrichment analysis found twelve signi cantly enriched pathways related to cancer progression, such as PI3K-Akt signaling pathway [23,24], ECM-receptor interaction [25,26] and p53 signaling pathway [27,28]. The results indicated that these DEGs played key roles in multiple cancer-related pathways, and further indicated that the DMSs might be involved in LUAD progression by regulating the corresponding gene expression.…”
Section: Functional Enrichment Of Dmgsmentioning
confidence: 84%